Gold prices and inflation - Greg Tkacz (Bank of Canada, 2007)
Using data for 14 countries over the 1994 to 2005 period, we assess the leading indicator properties of gold at horizons ranging from 6 to 24 months. We find that gold contains significant information for future inflation for several countries, especially for those that have adopted formal inflation targets. This finding may arise from the manner in which inflation expectations are formed in these countries, which may result in more rapidly mean-reverting inflation rates. Compared to other inflation indicators for Canada, gold remains statistically significant when combined with variables such as the output gap or the growth rate of a broad monetary aggregate.
Keywords: E31; E44; 330; Inflation and prices; Exchange rates; Gold; Inflationserwartung; Inflation Targeting; Welt